Progress in Colorectal Surgery - Beynon, John; Carr, Nicholas D. (Springer London : Imprint: Springer, 2005)
Progress in Colorectal Surgery covers a variety of topics of current interest to the colorectal specialist. Thirteen areas are covered by internationally renowned experts and include chapters on topics such as referral guidelines for rectal bleeding, difficult intra-operative problems in pelvic surgery, advances in the medical treatment of Crohn's disease, adjuvant treatment for colorectal malignancy, thorough overview of modern developments in the surgical treatment of disorders of the lower intestine including ulcerative colitis/severe acute colitis and innovations in the treatment of fecal incontinence. Recognizing that the surgeon does not work in isolation, the book also integrates recent progress in imaging techniques for the anal canal and rectum, and highlights medico-legal considerations. Aimed at current practitioners and trainees, the book discusses key concepts that will assist general surgeons and colorectal consultants in their management of patients with a broad spectrum of anorectal and colonic disorders. With a problem-oriented slant, this book is essential reading for all those with an interest in coloproctology.